Nurse Led Sedation: The Clinical and Echocardiographic Outcomes of the 5-Year Emory Experience. Issue 4 (3rd July 2020) - Keegan, Patricia; Lisko, John C.; Kamioka, Norihiko; Maidman, Samuel; Binongo, Jose N.; Wei, Jane; Vadlamudi, Ratna; Edwards, J. Kirk; Vatsa, Nishant; Maini, Aneesha; Reginauld, Shawn; Gleason, Patrick; et al.
ABSTRACT: Background: Our center has developed protocols for nurse-led sedation (NLS) where dedicated cardiac catheterization laboratory nurses directly provide sedation with fentanyl and midazolam. This study compares outcomes of patients undergoing minimalist TAVR with anesthesia led sedation (ALS) using monitored anesthesia (MAC) care delivered by a dedicated anesthesia team vs. sedation delivered by catheterization laboratory nurses (NLS). Methods: We reviewed each patient's medical record and divided them into two groups: those in whom the multi-disciplinary heart team chose NLS vs. anesthesia led sedation (ALS). Patients were propensity matched in a 2:1 fashion to compare clinical and echocardiographic outcomes. Results: Using a 2:1 propensity score matching, 407 patients who underwent TAVR under the NLS protocol were matched with 243 patients who underwent TAVR under the monitored anesthesia care pathway with ALS. In the NLS group, 2.2% of patients required conversion to general anesthesia, while 0.8% of patients in the ALS group underwent conversion ( p = 0.22). Similarly, 1% of patients required conversion to open surgery in the NLS group compared to 0.8% in the ALS group ( p = 0.99). Both groups had comparable survival to discharge (98.3% NLS vs. 100% ALS, p = 0.05). No mortality was directly attributable to anesthesia method. Discharge echocardiographic assessment of procedural success was similar between groups. Conclusions: NLS appears to have procedural outcomes similar to anesthesia-led moderate sedation. NLS is associated with significantly shorter procedure-room time and contrast volume than anesthesia-led moderate sedation. At 1 year, there was no difference in the combined endpoint of death or readmission between groups. Abbreviations: ALS: Anesthesia led sedation; ECMO: Extra corporeal membrane oxygenation; LOS: Length of stay; LVEF: Left ventricular ejection fraction; MAC: Monitored anesthesia care; NYHA: New York Heart Association; NLS: Nurse led sedation; PROM: Predicted Risk of Mortality; STS: Society of Thoracic Surgeons; TAVR: Transcatheter aortic valve replacement; VARC: Valve Academic Research Consortium